2022
DOI: 10.1093/ndt/gfac289
|View full text |Cite
|
Sign up to set email alerts
|

Design and population of the VALOR-CKD study: a multicenter, randomized, double-blind, placebo-controlled trial evaluating the efficacy and safety of veverimer in slowing progression of chronic kidney disease in patients with metabolic acidosis

Abstract: Background Whether treating metabolic acidosis slows progression of chronic kidney disease (CKD) has not been established. Veverimer is a novel hydrochloric acid binder that removes acid from the gastrointestinal tract leading to an increase in serum bicarbonate; it is being developed to treat metabolic acidosis with the goal of slowing progression of CKD. Methods The VALOR-CKD trial is an international, randomized, multicent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Mathur, et al (2023) 12 showed the patients' mean age was 65.1 years old, and female patients made up 42% of the total.…”
Section: Resultsmentioning
confidence: 99%
“…Mathur, et al (2023) 12 showed the patients' mean age was 65.1 years old, and female patients made up 42% of the total.…”
Section: Resultsmentioning
confidence: 99%
“…The statistical analysis plan and power calculations have been published previously, 10 and the complete prespecified statistical analysis plan is provided with the protocol (Supplemental Appendix). In brief, VALOR-CKD was an event-based trial that was designed to terminate when the independent blinded Clinical Events Adjudication Committee had positively adjudicated the requisite number of primary end point events.…”
Section: Methodsmentioning
confidence: 99%
“…The VALOR-CKD study was a randomized, double-blind, placebo-controlled, multicenter clinical trial; details regarding the trial design and baseline characteristics of the participants have been published previously, 10 and the protocol is available in the Supplemental Appendix. The trial was sponsored by Tricida, Inc. and conducted at 346 sites in 35 countries from September 2018 through September 2022.…”
Section: Trial Design and Oversightmentioning
confidence: 99%
See 1 more Smart Citation
“…A prespecified exploratory analysis demonstrated that veverimer was associated with improved time to the composite clinical endpoint of death, KRT, or a decline in eGFR of at least 50% in the 196 participants included in the cumulative 52 weeks treatment period. This culminated in the randomized multicenter randomized placebo-controlled VALOR-CKD trial, which recruited over 1400 patients [29 ▪ ]. Topline results were released by the parent company Tricida indicating that the study did not meet its primary endpoint, which was defined as time to first occurrence of any event in the composite of renal death, ESKD or greater than or equal to 40% reduction in eGFR.…”
Section: Veverimer As An Alternate Treatment To Sodium Bicarbonatementioning
confidence: 99%